Achieving strategic flexibility in the era of big data: The importance of knowledge management and ambidexterity. Issue 8 (23rd March 2020) - Rialti, Riccardo; Marzi, Giacomo; Caputo, Andrea; Mayah, Kayode Abraham
Abstract : Purpose: This research unpacks the micro-mechanisms that exist between an organisation's ability to conduct big data analytics (BDA) and its achievement of strategic flexibility. Knowledge management capabilities and organisational ambidexterity have long been considered factors influencing the aforementioned relationship. In order to assess this, the authors build on dynamic capabilities as the main theoretical lens through which to examine. Design/methodology/approach: Structural equation modelling (SEM) is the main methodological approach used in this research. A structural model was developed and tested based on 215 survey responses collected from managers of organisations in continental Europe. Findings: The results indicate that BDA capabilities are a significant antecedent of an organisation's strategic flexibility. This relationship, however, is influenced by knowledge management capabilities and ambidexterity. Practical implications: Managers wishing to properly exploit the potential of big data should invest in the elaboration of knowledge management processes across their organisation. This strategy can foster strategic flexibility. Originality/value: Previous research has explored the theoretical links between big data, knowledge management and strategic flexibility. However, little attention has been paid to the quantitative investigation of the phenomenon.